Comparing The Effect of Acromioclavicular and Sternoclavicular Joint Mobilization with and without Specific Active Exercises in Chronic Sub Acromial Impingement Syndrome: Randomized Control Trail - Umara Asif, Shakeel Ahmad, Huma Akhtar, Attiq Ur Rehman, Sidra Ali Naqvi, Farah Anwar, Sadaf Waris, (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: Shoulder Impingement Syndrome is one of the common musculoskeletal disorders. It leads to significant function restriction, pain and disability. Manual Physical therapy is a non-invasive risk-free approach for managing Sub-acromial Impingement Syndrome. The objective is to determine the effectiveness of Acromioclavicular and Sternoclavicular joint mobilization with and without specific active exercises in chronic sub-acromial impingement. Methodology: This Randomized control trail was conducted at Physical Therapy Department of Rawal Medical Point, Rawalpindi from November 2018 to February 2019. Inclusion criteria were both male and female patients with chronic shoulder pain for more than three months and age ranged between 30-55 years, while patients with history of trauma, bilateral shoulder pain, patients with RA, other systemic diseases and age less than 30 and greater than 55 were excluded. A total of 60 patients were selected in the study and were equally divided into two groups, i.e. A and B. Numeric Pain Rating Scale NPRS, Shoulder Pain and Disability Index SPADI, and Goniometry of Shoulder Range of Motion were used as assessment tools measured at baseline and at completion of 6week intervention. Data was analyzed through SPSS version 21. Results: Statistically the results of both techniques were significant (p<0.05) but Clinically the group of patients treated with acromioclavicular and sternoclavicular joint mobilization with specific active exercises improved pain NPRS post-intervention 1.83±0.647, function SPADI score post-intervention 23.394±4.717 and more improvement in ROM as compared with the group of patients treated with acromioclavicular and sternoclavicular joint mobilization alone having NPRS post-intervention 3.56±0.679 and SPADI score post-intervention 32.021±5.0962 showing improvement in pain and function with comparatively less improvement in ROM. Conclusion: It is concluded that if the patients with chronic sub-acromial impingement treated with acromioclavicular and sternoclavicular joint mobilization with specific active exercises, will manage symptoms like pain, restricted ranges and functions more effectively than treated with acromioclavicular and sternoclavicular joint mobilization alone.